2013
DOI: 10.1111/jcmm.12211
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous carcinoma of the head and neck – not a human papillomavirus‐related tumour?

Abstract: Association between verrucous carcinoma (VC) of the head and neck and human papillomaviruses (HPV) is highly controversial. Previous prevalence studies focused mostly on α-PV, while little is known about other PV genera. Our aim was to investigate the prevalence of a broad spectrum of HPV in VC of the head and neck using sensitive and specific molecular assays. Formalin-fixed, paraffin-embedded samples of 30 VC and 30 location-matched normal tissue samples were analysed, by using six different polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…Moreover, ␤-PV types can be detected in both immunocompetent and immunosuppressed individuals, not only in various cutaneous lesions but also in "healthy" skin and hairs plucked from different anatomical locations [13]. Surprisingly, it has recently been shown that ␤-PVs also infect the mucosal epithelium of the head and neck region and esophagus [3][4][5][6][7], as well as the mucocutaneous epithelium of the anal canal/edge [8], indicating a broader spectrum of epithelial tropism than previously appreciated for HPVs from the genus ␤-PV. However, the clinical significance of these infections remains elusive.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, ␤-PV types can be detected in both immunocompetent and immunosuppressed individuals, not only in various cutaneous lesions but also in "healthy" skin and hairs plucked from different anatomical locations [13]. Surprisingly, it has recently been shown that ␤-PVs also infect the mucosal epithelium of the head and neck region and esophagus [3][4][5][6][7], as well as the mucocutaneous epithelium of the anal canal/edge [8], indicating a broader spectrum of epithelial tropism than previously appreciated for HPVs from the genus ␤-PV. However, the clinical significance of these infections remains elusive.…”
Section: Discussionmentioning
confidence: 97%
“…␤-PVs are etiologically associated with epidermodysplasia verruciformis, a rare autosomal recessive hereditary disorder that is characterized by chronic ␤-PV infection and subsequent development of cutaneous squamous cell carcinoma. An etiological role of ␤-PV in the development of precancerous lesions and cancer of the skin in organ-transplant patients, as well as in immunocompetent individuals, has also been recently suggested [3][4][5][6][7]. Moreover, we recently co-characterized a novel ␤-PV type (HPV-120; ENA http://dx.doi.org/10.1016/j.jcv.2014.07.009 1386-6532/© 2014 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, it appears that VSCC of the head and neck (Fig. 2a) is not associated with infection with HPV [34][35][36].…”
Section: Etiopathogenesis Of Conventional Squamous Cell Carcinoma Sumentioning
confidence: 89%
“…Total DNA was extracted from five 10 µm thick sections of each paraffin tissue block, as described previously 13. In order to prevent tissue contamination, the microtome blade and surface were extensively cleaned after each sectioning with xylene and DNA Remover solution (Minerva Biolabs, Berlin, Germany).…”
Section: Methodsmentioning
confidence: 99%